The question of methodological naturalism - Blum, Jason N. 1977- (Supplements to method & theory in the study of religion, 2018)
"The traditions and institutions that we call religions abound with references to the supernatural: ancestral spirits, karma, the afterlife, miracles, revelation, deities, etc. How are students of religion to approach the behaviors, doctrines, and beliefs that refer to such phenomena, which by their very nature are supposed to defy the methods of empirical research and the theories of historical scholarship? That is the question of methodological naturalism. The Question of Methodological Naturalism offers ten thoughtful engagements with that perennial question for the academic study of religion. Contributors include established senior scholars and newer voices propounding a range of perspectives, resulting in both surprising points of convergence and irreconcilable differences in how our shared discipline should be conceptualized and practiced"...